Strategi Pelayanan terhadap Pelanggan di PT Balai Mandiri Prasarana Palembang - Asriadi Akmal; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled Service Strategy for Customers at PT Balai Mandiri Prasarana Palembang. Every company certainly needs a strategy in terms of service, such as PT Balai Mandiri Prasarana Palembang which requires a service strategy with the aim of providing customer satisfaction with the services provided. This study aims to determine the service strategy for customers at PT Balai Mandiri Prasarana Palembang. This study uses a qualitative approach, with data sources namely primary and secondary data, the subjects of this study amounted to 5 participants including Branch Heads (1 person), Staff (2 people), and Administrative Employees (2 people). Data collection techniques used are interviews, observation and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The conclusion of this study is related to the service strategy used by PT Balai Mandiri Prasarana Palembang to provide customer satisfaction with the services provided, which include: First, physical evidence, such as appearance by providing services by dressing neatly and in accordance with regulations, while for communication facilities, such as using office facilities and using personal cellphone facilities. Second, reliability such as the reliability of employees in conveying information by explaining it at the beginning of registration with the aim that customers believe, understand and understand. Third, responsiveness is like employee service in serving customers by providing good service that makes the customers happy and comfortable. The four guarantees include instilling trust in customers and providing good facilities to their customers. The five empathy are like paying attention to customers to help customers who need help.